Multifocal electroretinogram evaluation of different optical coherence tomography patterns of diabetic macular edema - Abdelrahman W.M. Mohamed; Yehia M. Khairat; Heba R. AttaAllah; Amr A.M. Abdelrahman (Journal of the Egyptian Ophthalmological Society)
Purpose To correlate macular function to morphological patterns of diabetic macular edema (DME) observed by optical coherence tomography (OCT). Patients and methods This study included 100 DME eyes and 60 control eyes. OCT patterns of DME were divided into: Type 1: diffuse retinal thickening (DRT); Type 2: cystoid macular edema (CME); Type 3: neurosensory detachment (NSD); and Type 4: the combined type that was further subdivided into: Type 4a: DRT with CME, Type 4b: DRT with NSD, and Type 4c: CME with NSD. These types were correlated with LogMAR VA and P1 wave amplitude and implicit time of multifocal electroretinogram. Results In both central ring 1 and paracentral ring 2, P1 amplitude was significantly reduced in all types of DME compared with control group. P1 amplitude was highest in Type 1, and lowest in Type 4c compared with other DME types. P1 implicit time was significantly delayed in all types, and significantly delayed in Type 4c compared with Type 1. Conclusion DRT was the best type for macular function, CME was associated with decreased P1 wave amplitude in central macular ring, NSD was associated with decreased P1 wave amplitude in the paracentral macular ring, combined CME with NSD carried the poorest visual function. From a practical point of view, combining OCT and multifocal electroretinogram testing may offer a potent method to assess the degree of retinal injury.